Teledermatology during the COVID‐19 pandemic: Experience at a tertiary care centre in North India - Handa, Sanjeev (Dermatol Ther, 2021)
BACKGROUND: Teledermatology has evolved as a valuable option to outpatient visits during the current pandemic. We set up a smartphone‐based hybrid model of teledermatology services providing direct care to patients at our center. To analyse patient and physician‐experience and acceptability for teledermatology over a 6‐month‐period, along with clinicodemographic profile of patients. METHODOLOGY: Single‐center, retrospective study conducted from May 20, 2020 to October 31, 2020. Patient satisfaction level for teledermatology was assessed on a 4‐point scale and compared with the satisfaction level during their previous physical visits prior to COVID‐19 pandemic. A physician assessment form was utilised to record the experience of dermatologists while providing teledermatology services. RESULTS: Of 7530 patients registered, a successful consult was provided to 6125 patients (81.34%). Average number of teleconsultations/day rose from 23.60 in May 2020 to 77.96 in October 2020. Mean age of patients availing teledermatology services was 33.60 ± 16.99 years. Average distance to care and travel time were 100.90 ± 171.77 km and 135 ± 222.32 min, respectively. A definitive diagnosis could be ascertained in 5724 patients (93.45%) and in‐person visit was recommended to 133 patients (2.2%). Out of 6125 patients, 5229 could be contacted for feedback, 935 (18.18%), 2230 (42.65%), 1749 (33.45%), and 300 patients (5.70%) reported being very satisfied, satisfied, partially satisfied, and unsatisfied, respectively. Of 1914 patients, who had availed in‐person OPD facilities prior to the pandemic, 914 patients (49.62%) preferred in‐person visits. Of 34 dermatologists surveyed, 88.2% felt comfortable providing teleconsultations and 82.4% felt the need to continue teledermatology services in the upcoming months. CONCLUSIONS: Overall, teledermatology is a valid alternative for in‐person dermatology visits during the current crisis; helping with initial triage and further patient management. Further refinement of the process could lead to even more acceptability.